Influence of genotype and paratype factors on the reproductive qualities of mother breeds of pigs - Kremez, Mykola; Кремез, Микола; Povod, Mykola; Повод, Микола Григорович; Mykhalko, Oleksandr; Михалко, Олександр; Izhboldina, O. O.; Izhboldina, O.; Izhboldina, Е. А.; Izhboldina, Н.; Izhboldina, Е.; Izhboldina, Olena; et al. (University of Agronomic Sciences and Veterinary Medicine of Bucharest - Faculty of Management and Rural Development, 2023)
The object of the research was the study of the influence of the breed of pigs and methods of their breeding on the reproductive functions of sows. Manifestation of various forms of the effect of hybrid power during direct and reverse crossing of animals of these breeds, as well as the tightness and directionality of correlative relationships were studied. The weight of one piglet at weaning was probably higher in purebred litters of the Landrace breed compared to other investigated genotypes. As a result of the research, it can be asserted that there is a medium-strength correlation between the weight of the litter of piglets at birth and their weight at weaning. Об’єктом дослідження було вивчення впливу породи свиней та методів їх розведення на репродуктивні функції свиноматок. Прояв різноманітних форм ефекту гібридної влади під час прямого та зворотне схрещування тварин цих порід, а також тіснота і спрямованість кореляційних зв'язків були вивчені. У результаті проведеного дослідження можна стверджувати, що існує кореляція середньої сили між масою приплоду поросят при народженні та їх масою при відлученні.
Вплив генотипових і паратипових факторів на репродуктивні якості материнської породи свиней
Іжболдіна Олена Олександрівна https://orcid.org/0000-0002-8816-2228
Keywords: pork production; виробництво свинини; pigs; свині; Irish breeding; ірландська селекція; reproductive capacity; відтворна здатність; breeding methods; методи розведення; heterosis effect; ефект гетерозису; industrial production; промислове виробництво